2005
DOI: 10.1021/jf051070y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Population, Age, and Cultivation Methods on Ginsenoside Content of Wild American Ginseng (Panax quinquefolium)

Abstract: Genotype and environmental effects on ginsenoside content among eight wild populations of American ginseng (Panax quinquefolium) were investigated. Root concentrations of six ginsenosides were determined at the time of collection of plants from the wild (T0) and 2 years (T2) after transplanting roots from each of the eight populations to each of two different forest garden locations. Both location and population had significant effects on root and shoot growth. Overall, ginsenoside Rb1 was most abundant, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
119
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(133 citation statements)
references
References 17 publications
8
119
3
Order By: Relevance
“…This information is very important, especially in the vegetable crops research, for obtaining the most valuable plant material with optimum nutritional components for proper harvesting or breeding strategies. 44,45) Our results have revealed the highest accumulation of total saponin content (mg/g dw) in the root-basal stem, ranging between 12.26 and 15.42, followed by that in the leaf, ranging from 5.10 to 8.97, and the lowest detected in the bulb, ranging from 4.6 to 5.33 (Fig. 3).…”
Section: Saponinsmentioning
confidence: 65%
“…This information is very important, especially in the vegetable crops research, for obtaining the most valuable plant material with optimum nutritional components for proper harvesting or breeding strategies. 44,45) Our results have revealed the highest accumulation of total saponin content (mg/g dw) in the root-basal stem, ranging between 12.26 and 15.42, followed by that in the leaf, ranging from 5.10 to 8.97, and the lowest detected in the bulb, ranging from 4.6 to 5.33 (Fig. 3).…”
Section: Saponinsmentioning
confidence: 65%
“…Ginseng is believed to produce various effects, including suppression of the growth and metastasis of cancer cells and activation of glutathione peroxidase and superoxide dismutase to protect against damage caused by free radicals, as well as decreasing malondialdehyde levels and increasing the activity of catalase. Also, non-saponins in red ginseng may improve learning and memory, while acidic polysaccharides activate can natural killer cells and increase the production of interferons [21,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…All ginsenosides have the same structure of four trans-ring rigid steroid skeleton with the difference in their number and site of attachment of hydroxyl groups (Gillis 1997, Attele et al 1999. Ginsenoside Rb 1 is the most abundant one among more than 20 ginsenosides in ginseng root despite different sources and species (Attele et al 2002, Washida & Kitanaka 2003, Lim et al 2005. Our recent study showed that ginsenoside Rb 1 , (Washida & Kitanaka 2003), facilitated adipogenesis of 3T3-L1 preadipocytes by enhancing peroxisome proliferator-activated receptor g 2 (PPARg2) and CCAAT/enhancer-binding protein a gene expression.…”
Section: Introductionmentioning
confidence: 99%